Respostas fisiológicas de Theobroma cacao L. a diferentes concentrações de ferro sob alagamento - Braga, Priscila da Conceição de Souza (2015)
Flooding is a limiting barrier for the initial growth and cocoa establishment in places subject to periodic flooding, given that it can cause changes in leaf gas exchange, nutrition and in optimum conditions of plant growth. Furthermore, they have been found large amounts of Fe in the irrigation water cocoa culture, and, under flooding conditions, the availability of this element in the plant is increased, generating a double stress condition. In this context, the aim of this study was to evaluate the effects of different concentrations of iron in the presence and absence of aeration in different cacao genotypes. We evaluated two cacao genotypes, TSH 1188 and SIAL 70, with and without aeration and excess iron, an experiment installed in a randomized block design with three replications and treatments distributed in a factorial arrangement (2x2x3) consisting of two genotypes, with and without aeration and three Fe concentrations: 44.5 µmol L-1 (recommended dose); 133.5 µmol L-1 (high dose) and 400.5 µmol L-1 (very high). Were evaluations of oxidative enzyme activity and the content of total soluble phenols, chlorophyll indices a, b and total and gas exchange at leaf level, mineral composition of leaves and growth. The enzymatic activity and total soluble phenolic content increased at the highest dose of Fe without aeration for TSH 1188 genotype (36.2% of guaiacol peroxidase and 205.1% for phenols). In SIAL 70 genotype the above the recommended doses promoted higher enzymatic activity of the peroxidase guaiacol with aeration and Polyphenoloxidase without aeration. The contents of chlorophyll a, b and total, were affected to a greater extent by iron stress for both genotypes, however, the TSH 1188 genotype had higher chlorophyll content. The gas exchange were altered adversely due to the excess iron and lack of aeration, and the photosynthetic rate for TSH 1188 genotype without aeration at the highest dose of iron decreased from 45.0% to 18.1 days, however at the end of 35th day recovered 94.1% of the initial photosynthetic rate. SIAL 70 genotype, this reduction was observed due to the excess iron independent of interference from aeration. The stomatal conductance and transpiration were reduced by the independent Fe excess of environmental conditions (aeration) for the two genotypes, and for the internal concentration of CO2 that result was observed only in TSH 1188 genotype. The nutrient absorption was also amended by excess iron and aeration. TSH 1188 genotype showed the highest growth when compared to SIAL 70 genotype, with the highest concentration of Fe (400.5 µmol L-1), independent of environmental conditions, there was an increase in dry mass in relation to the recommended dose iron. Depending on the results, the two cocoa genotypes tolerance absence of aeration and iron overload, however, it was found different mechanisms to handle each type of stress.